2016
DOI: 10.17265/1934-8975/2016.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of Spark Ignited Engine Fueled with Gasoline-Ethanol-Methanol Blends

Abstract: Abstract:In this paper, experimental investigations are presented to assess the performance variations in a single cylinder spark ignited engine when run with three different gasoline-alcohol blends: (88% gasoline-12% methanol, 88% gasoline-12% ethanol and 88% gasoline-6% methanol-6% ethanol). Additional tests are carried out with the basic gasoline fuel for comparison analysis and performance assessment. Engine performance is investigated under a variety of engine operating conditions. The results are present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Since this decreasing engine output power value is obtained with the same amount of fuel, the BTE values of the engine are also decreased in the calculations. In the literature, some researchers have reported that due to the high evaporation temperature of bioethanol in the combustion chamber cannot be achieved in the homogeneity of the mixture so the use of bioethanol decreased BTE values [22,23].…”
Section: Engine Performance Parametersmentioning
confidence: 99%
“…Since this decreasing engine output power value is obtained with the same amount of fuel, the BTE values of the engine are also decreased in the calculations. In the literature, some researchers have reported that due to the high evaporation temperature of bioethanol in the combustion chamber cannot be achieved in the homogeneity of the mixture so the use of bioethanol decreased BTE values [22,23].…”
Section: Engine Performance Parametersmentioning
confidence: 99%
“…In the current study, BSFC increased by 3.67% and 1.97% for E5M5 and E10, respectively, compared to pure gasoline. Kamil and Nazal [56] found that decreases in BSFC of 10%, 14% and 18.4% in the cases of E6M6, M12 and E12, respectively.…”
Section: Comparative Assessment Of Engine Performancementioning
confidence: 98%
“…In the current study, BSFC increased by 3.67% and 1.97% for E5M5 and E10, respectively, compared to pure gasoline. Kamil and Nazal [56] found that decreases in BSFC of 10%, 14% and 18.4% in the cases of E6M6, M12 and E12, respectively. BTE is a measure how efficiently the engine converts the fuel's heat energy into useful mechanical work, which is expressed as a percentage.…”
Section: Comparative Assessment Of Engine Performancementioning
confidence: 98%
“…This result was consistent with previous research. showing that the addition of alcohol groups improved engine performance [40]. Cycle variation on the combustion process is necessary because two reason.…”
Section: Torquementioning
confidence: 99%